Raindrop axis ratios and size distributions in Florida rainshafts: an assessment of multiparameter radar algorithms - Xiao, Rongrui, author; Chandrasekar, V., author; Bringi, V. N., author; IEEE, publisher (Colorado State University. Libraries, 1998)
Eleven penetrations of rainshafts by the University of Wyoming King Air (WKA) aircraft equipped with a two-dimensional (2-D) optical array probe are studied in coordination with multiparameter radar measurements from the National Center for Atmospheric Research (NCAR) CP-2 radar collected in a multicellular storm that occurred on August 8, 1991, of the Convective and Precipitation/Electrification (CaPE) experiment. A comparison is made between the mass-weighted mean diameter (Dm) and rainrate (R) computed from the nine-size spectra and their estimates from multiparameter radar algorithms based on Zdr and Zh. It was found that Dm could be estimated with a mean bias of 0.07 mm and a standard deviation of 0.35 mm. Rainrates (in the range of 10-60 mmh-1) could be estimated from Zh and Zdr with a mean bias of 1-4% and fractional standard error (FSE) of 30-40% depending on the estimator used. Raindrop axis ratios are analyzed as a function of volume equivalent spherical diameter (Deq) in the range 2-6 mm. The mean axis ratio versus the Deq relationship was found to be consistent with previous data from the High Plains (from Colorado and Montana). A study of fluctuations of axis ratio (about their mean value) showed that most drops have axis ratios close to their mean values with oscillation amplitudes to be typically ±10% in axis ratio, again consistent with the earlier High Plains results.
Keywords: size distributions; raindrop; radar; multiparameter